Shortwave multichannel information fusion method based on DSmT evidence discount theory - Junbing LI; Xiaoping ZENG; Guojun LI; Changrong YE (Tongxin xuebao, 2024)
In response to the problem of poor performance of classical fusion methods in combining multiple shortwave channel information due to the complexity and harshness of shortwave channels and prominent conflicts among channel in-formation, a shortwave multi-channel information fusion method based on the DSmT evidence discounting theory was pro-posed.The DSmT evidence discounting theory was employed as the fusion framework to achieve fusion, inference, and de-cision-making of multiple shortwave channel information.Firstly, the relative envelope standard deviation of the OFDM frame was normalized, and the discount weight was calculated through the relative envelope standard deviation and the dis-count factor.Then, the bit soft information extraction function was used to obtain the bit probability, which was quantita-tively assigned to the basic belief assignment function as evidence.Finally, the PCR6 fusion rule was applied to fuse, infer, and make decisions on the soft information from multiple channels.Simulation experiments comparing the proposed method with classical fusion methods under various channel conditions and modulation schemes indicate significant gains in bit error rate and packet error.